2019
DOI: 10.1186/s13765-019-0456-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the nutrient composition and statistical profile in red pepper fruits (Capsicums annuum L.) based on genetic and environmental factors

Abstract: Red peppers are a remarkable source of nutrients in the human diet. However, comprehensive studies have not reported on the effects of genotype, cultivation region, and year on pepper fruit characteristics. To address this, 12 commercial pepper varieties were grown at two locations in South Korea, during 2016 and 2017, representing four environments, and concentrations of proximate, minerals, amino acids, fatty acids, capsaicinoids, and free sugars in pepper pericarps were determined. Variation in most nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
2
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 28 publications
3
18
2
1
Order By: Relevance
“…The same authors observed that the ash content varied between 4.27% and 4.68% [21] and between 5.3% and 7.3% [24]. The mentioned values are in good agreement with our values, although other studies reported much higher values of both protein and ashes [25].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The same authors observed that the ash content varied between 4.27% and 4.68% [21] and between 5.3% and 7.3% [24]. The mentioned values are in good agreement with our values, although other studies reported much higher values of both protein and ashes [25].…”
Section: Discussionsupporting
confidence: 93%
“…It was found that K concentrations are higher in GP, regardless of agricultural practices, while P concentrations are higher in RP, which partially agrees with the data [23]. The analysis of 12 varieties of RP grown in two different regions of South Korea [25], showed that the average levels of Fe in the Imsil (IS) and Youngyang (YY) regions were 6.1 mg 100 −1 and 6.6 mg 100 −1 respectively. Regarding Ca, the same authors point out the mean values of 114 mg 100 −1 in IS and 104 mg 100 −1 in YY, while for K the mean concentrations were 2821 mg 100 −1 (IS) vs. 4125 mg 100 −1 (YY), levels quite concordant with those detected in the current work.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…These distinctions could be due to the difference of cultivar and analysis methods. Previous studies also did not detect Gln, Asn, and GABA in 12 pepper cultivars planted in South Korea (Kim et al., 2019). Marina, Alba, Joan, Marta, and Magdalena (2014) reported that LAB could produce GABA naturally.…”
Section: Resultsmentioning
confidence: 79%